Leaching of Rare Earth Elements from Various Sources - Han, Kenneth N. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The proposed book is a compilation of a Special Issue on "Leaching of Rare Earth Elements from Various Sources", published in the journal Minerals in 2020. There are 10 papers contributed by experts in the area, and these can be grouped into four categories: leaching from low-grade ores including coal, clay, soil, and red mud; pre-treatment and leaching; recycling; and precipitation and nano-hydrometallurgy. Although these articles are available in the journal Minerals, it is convenient to compile the most valuable information into a book form so that scholars and industrial practitioners can have easy access to it when they need it where the Internet is not easily available. I strongly believe that the book on a very specialized topic matter such as modern extraction technologies of rare earth elements will contribute greatly to the fast-growing industry that needs rare earth elements.